An Analysis of the Special Safeguard Mechanisms in the Doha Round of Negotiations: A Proposed Price-trigger-based Safeguard Mechanism - Parthapratim Pal; Deepika Wadhwa (Indian Council for Research on International Economic Relations (ICRIER), 2006)
In the Doha Round of negotiations on agriculture it has been decided that all developing and least developed Member countries of the WTO will have access to a Special Safeguard Mechanism (SSM). This means that developing countries will now have the option to temporarily impose higher tariff rates on the import of an agricultural product if there is either a surge in its import volumes or a sharp dip in its import prices. However, the exact mechanisms of the implementation of SSMs have not been spelt out. It is also not clear what legal provisions the Member countries will have to follow to use this safeguard mechanism. This paper takes a detailed look at the SSM and analyzes its usefulness for developing countries. It also explores how the concept of a special agricultural safeguard has evolved in the present round of negotiations and what are the country positions on SSMs in the Doha Round. The paper then proposes a price-trigger-based SSM instrument which is consistent with the goals spelt out in the Doha Development Agenda and satisfies most of the desired features of a safeguard instrument.
Keywords: F13; Q17; 330; WTO; Agriculture; Volatility; Special safeguards; Tariff rates